Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/s0049-3848(16)30090-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting clotting proteins in cancer therapy – progress and challenges

Abstract: Cancer-associated thrombosis remains a significant complication in the clinical management of cancer and interactions of the hemostatic system with cancer biology continue to be elucidated. Here, we review recent progress in our understanding of tissue factor (TF) regulation and procoagulant activation, TF signaling in cancer and immune cells, and the expanding roles of the coagulation system in stem cell niches and the tumor microenvironment. The extravascular functions of coagulant and anti-coagulant pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 117 publications
2
28
0
Order By: Relevance
“…Vimentin silencing also decreased the ability of tumor cells to accomplish metastatic colonization when injected as CTCs in experimental metastasis assays. These data bridge two independent sets of literature data including ours supporting, on one hand, that EMT-shifted CTCs represent a subpopulation of CTCs with enhanced metastatic competence and, on the other hand, that TF-dependent coagulant properties of CTCs facilitate their survival in the blood stream and metastatic colonization [10][11][12]30]. Accordingly, we previously reported the existence of CTCs co-expressing vimentin and TF in the blood of breast cancer patients [21].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Vimentin silencing also decreased the ability of tumor cells to accomplish metastatic colonization when injected as CTCs in experimental metastasis assays. These data bridge two independent sets of literature data including ours supporting, on one hand, that EMT-shifted CTCs represent a subpopulation of CTCs with enhanced metastatic competence and, on the other hand, that TF-dependent coagulant properties of CTCs facilitate their survival in the blood stream and metastatic colonization [10][11][12]30]. Accordingly, we previously reported the existence of CTCs co-expressing vimentin and TF in the blood of breast cancer patients [21].…”
Section: Discussionsupporting
confidence: 85%
“…Several pieces of work support a contribution of coagulation in the process. Hypercoagulability is actually a long known correlate of malignancy and venous thromboembolism has been associated with worse prognosis [10][11][12]. In particular, CTCs have recently been associated with increased risk of venous thrombosis in cancer patients [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although coagulation disorders in individuals with cancer are multifactorial in origin, several studies have reported the important role of coagulation activity in cancer progression (16,17). Vitamin K, a fat-soluble vitamin, is necessary for the blood coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies point out that blood coagulation proteins develop an important role in tumor progression [ 37 ]. These works discussed the impact of the activation of the blood clotting cascade on primary tumor growth [ 38 ], tumor metastasis and cancer-associated thrombosis [ 39 ] and antitumor therapies that target blood-coagulation-associated proteins [ 40 ].…”
Section: Discussionmentioning
confidence: 99%